THE INFLUENCE OF THE IDEAS OF THE HURUFISM SECT ON NASIMI’S WORK - Kadirovna, Amonova Zilola; Oxunjonovna, Safarova Khilola; Bakaevna, Radzabova Ma’rifat (The journal of contemporary issues in business and government, 2021)
The article deals with the influence of hurufism, one of the mystical sects, on the work of the great poet ImodiddinNasimi. Also, the verses of the poet written under the influence of literacy are analyzed from the ideological and artistic point of view.Nasimi expresses his thoughts and feelings in a simple and popular way. That is why the poet’s poems are close to the heart. While these poems may seem simple and straightforward at first glance, they are deep in content and artistically high. It is no exaggeration to say that Nasimi’s work was one of the reasons for the spread of the ideas of the Hurufi sect among the people. He focused on the inner meanings of the Arabic alphabet, the equality of the human face with the mushaf, and the divinity of man.